A influência do credenciamento e da avaliação institucional para a modalidade de educação a distância no modelo de gestão de uma instituição de ensino superior - Tagliaferro, Manoela Pierina (2016)
The process of managing the category of distance learning in an institution of Higher Education requires intelligence, planning, academic reorganization and a paradigm shift of the actions used until now, for the on-campus category. It is a matter of legal requirement as well as of competitiveness, so the private Higher Education Institutions can look for innovation as a strategy for their academic managerial processes. The present research had as objective to identify to what extent the accreditation and the institutional evaluation provoked changes or innovations in the managing model of a certain private Higher Education Institution for the offer of distance learning category. The research approach was qualitative, of applied nature and for exploratory reasons. The techniques used for data collection were documental analysis, semi-structured interview and participant observation. To reach the proposed objective, a comparative research of the managing model of the Higher Education Institution was made, comparing its situation before and after the accreditation for the category of distance learning. The indicators of the Institutional Accreditation Instrument for the Category of Distance Learning of the Ministry of Education served as analysis units for the comparison and the institutional documents served as data sources. The result obtained with the comparison was incorporated to the data of the transcribed interviews and to the participant observation, presenting, then, a final image of the indicators that suffered changes, innovations and even showing which indicators have not changed at all. The research had as result the identification of innovation in the integration of the categories, the diversification of teaching methods and the offer of on-line academic services. We realized changes such as the creation and implementation of a policy of operational working for the category of distance learning and the restructuring of the department that was responsible for its implementation. Consequently, the management of the given areas was affected in function of the necessity to attend, in a fast manner, to the new category and to the integration between on-campus and distance learning, and an innovation of the systems and processes was noticed.